Sistem Auto Recommendation Objek Wisata Menggunakan Metode SAW - Murti, Alif Catur; Chamid, Ahmad Abdul (JSINBIS (Jurnal Sistem Informasi Bisnis), 2018)
The tourism sector is a complex multidimensional sector, which has an influence over the interrelation of other sectors in tourism activities and now the tourism sector is concerned by the government. Every tourist who will visit the tourist sites must have some consideration. The fact that today is happening is a lot of tourists who are disappointed because the destination is not in accordance with what they want. Seeing that the media campaign that is currently done is still not efficient, so Auto Recommendation System is needed which is capable to do visualized in digital mapping, and the system built can show the automatic recommendation of tourist destinations in accordance with the wishes of tourists. Auto Recommendation System is a system that implements Simple Additive Weighting (SAW) method. The results of this research factors other than the value of weight given by tourists, is the value factor owned by each alternative for each criteria, because the higher the value owned by the higher the higher the value of the final ranking obtained by the alternative. The end result of the SAW method is in the form of alternative ranking of existing tourism objects. Based on the results of these rankings the system also produces output in the form of location maps along with detailed information of the tourism object. Religious tourism Sunan Kudus and Sunan Muria became the recommended tourist attraction with first and second priority.